2011
DOI: 10.2172/1012465
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Technetium Interactions With Reducing Cementitious Materials

Abstract: Revision 0 can oxidize technetium in a portland cement or saltstone-like monolith. The shrinking core model used in the saltstone performance assessment describes the existence of an oxidized outer layer of concrete surrounding a shrinking core of reducing intact saltstone. A sharp boundary between the two zones moves slowly inward, resulting in oxidation of Tc(IV). This work largely reinforced our conceptual model of the shrinking core model, but more importantly provided clarity regarding process kinetics, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Previous desorption studies by Kaplan et al (2008) reported K d values similar to those measured for this report where they measured a K d in an oxidizing environment of 0.93 mL/g and a reduced value of 91.3 mL/g, although there is some question to the validity of the latter value because of interference in the analytical data used to calculate the K d (Kaplan et al 2008). In a kinetic study, Kaplan et al (2011) measured steadily increasing technetium K d values from 2 to 900 mL/g as the contact time of Tc(VII) increased from 1 to 56 days. In these latter studies, a glovebox was used and atmospheric O 2 was maintained much lower <0.5 ppm, (this work 30-60 ppm), and suspension Eh was typically -250 mV.…”
Section: Technetiumsupporting
confidence: 78%
See 3 more Smart Citations
“…Previous desorption studies by Kaplan et al (2008) reported K d values similar to those measured for this report where they measured a K d in an oxidizing environment of 0.93 mL/g and a reduced value of 91.3 mL/g, although there is some question to the validity of the latter value because of interference in the analytical data used to calculate the K d (Kaplan et al 2008). In a kinetic study, Kaplan et al (2011) measured steadily increasing technetium K d values from 2 to 900 mL/g as the contact time of Tc(VII) increased from 1 to 56 days. In these latter studies, a glovebox was used and atmospheric O 2 was maintained much lower <0.5 ppm, (this work 30-60 ppm), and suspension Eh was typically -250 mV.…”
Section: Technetiumsupporting
confidence: 78%
“…A concern is that the slightest amount of O2 oxidizes the Tc(IV) to Tc(VII). In a kinetic study, Kaplan et al (2011) measured steadily increasing Tc Kd values from 2 to 900 mL/g as the contact time of Tc(VII) increased from 1 to 56 days. In these latter studies, a glovebox was used and atmospheric O2 was maintained much lower, <0.5 ppm, and suspension Eh was typically -250 mV.…”
Section: Boron (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is immobilized in saltstone by (1) minimizing diffusion within the pore spaces of the cementitious wasteform, and (2) promoting the reduction of the highly mobile Tc(VII) form to a highly immobile Tc(IV) form by blast furnace slag. Kaplan et al (2011; reporting the thesis work by Lilley (2010)) attempted to measure its equilibrium constant by conducting (ad)sorption TcO 4 -studies in a glovebag. The objective was to measure the distribution coefficient, K d value, between solid phase saltstone and the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%